Tax behaviour relating to the review of a revised regional tax policy: A study in Greece - Nikolaos Varotsis; Ioannis D. Katerelos (Journal of Economic Structures, 2020)
The failure over time of the tax system in Greece to harmonize with a sound and efficient fiscal mix raises questions about the possibility of a radical restructuring. The last decade of continuous tax reforms has neither particularly restricted the black economy nor provided the government with fresh fiscal resources, and it has outgrown its arrears. A socially acceptable fiscal policy may lead to a new, sound fiscal policy mix. Tax restructuring that strengthens the tax base at the regional, local or European level-compared to its structuring at the one-sided governmental level to date-may be a key factor in the social acceptance of a new tax system. The degree of tax decentralization of the applied tax policy is likely to improve fiscal order and management on the one hand and, on the other hand, enhance tax revenues by enhancing tax compliance.
Keywords: 330; Regional tax; Public finance; Fiscal policy; Tax restructuring; Tax behaviour